Layout-Oriented Design of a 60 GHz Power Ampliﬁer in SiGe Technology - Sette, Elmo Luiz Fechine (2018)
This work presents the design of a fully integrated cascode single-stage power ampliﬁer for 60 GHz band. The technology used in the design was Global Foundries SiGe of 0.13µm (BiCMOS8HP). A load-pull analysis of the cascode was done including optimization of the bias and geometry parameters aiming at ﬁnding the best performance of this topology. A layout-oriented design approach was adopted to decide upon diﬀerent combinations/arrangements of passive components and interconnections, aiming at reducing the global losses and, thus, increasing the energy eﬃciency of the ampliﬁer. Post-layout simulations show a saturated output power of 19.32 dBm, 27.8% of power added eﬃciency (PAE) and a power gain of 10.4 dB at 60 GHz. The ampliﬁer consumes 63 mA from a 4.4 V power supply and occupies an area of approximately 0,475 mm2. The circuitwastaped-outinlate2017.Experimentalresultsarepresentedattheendofthetext.